Impact of A Short-Term, Mindfulness-Based Stress Reduction Program on the Well-Being of Infertile Women: A Mixed-Method Study. Issue 4 (October 2015) - Paiva, Sara P.C.; Nery, Simone F.; Magalhães, Estefânia B.; Couto, Bráulio G.M.; Amaral, Clara A.V.; Campos, Fernanda M.F.; Camargos, Aroldo F.; Reis, Fernando M.
Background: Mind-body skills groups represent an experiential approach to teaching antistress techniques that can enable a person to achieve mindfulness, self-awareness and self-reflection, to engage in self-care. This study examined whether a short-term mindfulness-based stress reduction (MBSR) program improved the well-being of infertile women. Methods: A cohort of 25 women was enrolled at a public academic center of reproductive medicine, while on the waiting list for in vitro fertilization (IVF). The MBSR intervention consisted of 12 weekly sessions of mindfulness meditation, relaxation, autogenic training, biofeedback and guided imagery. The participants completed a qualitative, open-ended questionnaire and the Psychological General Well-Being Index (PGWBI) questionnaire to assess anxiety, depressed mood, positive well-being, self-control, general health and vitality, before and after the intervention period. Data were analyzed by paired t- test and by 95% confidence interval. Results: The qualitative analysis revealed 5 central themes in patients' responses to the questionnaires: connections, self-discovery, stress relief, learning and consciousness. Total PGWBI score increased by 17% (mean difference 14.1 ± 3.9 points, p<0.01), and all subscales improved after the intervention course compared with the preintervention values. Conclusions: Both qualitative and quantitative assessment suggest that a 12-week MBSR program may improve the general well-being of infertile women awaiting IVF.